Left ventricular mechanical dispersion by speckle tracking echocardiography is a predictor of atrioventricular block after transcatheter aortic valve implantation. (3rd October 2022) - Kaya, E; Andresen, K; Lie, O H; Aaberge, L; Haugaa, K; Edvardsen, T; Skulstad, H
Abstract: Background: Transcatheter Aortic Valve Implantation (TAVI) is an effective therapy for patients with severe aortic stenosis (AS). Complete atrioventricular block (AVB) that requires permanent pacemaker implantation is a common complication of TAVI. Direct mechanical effect of the prosthetic valve, QRS duration and underlying myocardial fibrosis are proposed mechanisms of AVB after TAVI. Left ventricular mechanical dispersion (LVMD) by Speckle Tracking Echocardiography (STE) is an index of contraction heterogeneity and a marker of myocardial fibrosis. Purpose: We aimed to evaluate the association between LVMD, QRS duration and AVB to assess markers used to predict AVB after TAVI. Methods: A total of 163 consecutive TAVI patients were enrolled in the study. Echocardiograms andelectrocardiograms were recorded the day before TAVI procedure to assess global longitudinal strain (GLS), LVMD and QRS duration. AVB and pacemaker (PM) implantation information was obtained by telephone interviews three months after TAVI. Results: Ten patients were excluded due to poor image quality. Of the 153 patients analyzed, 45% were female. Mean age was 80±7 years. In our patient cohort 15.7% of the patients received PM within three months after TAVI. GLS and QRS duration was not different between AVB group and No-AVB group (−15.8±4.5% vs −16.9±4.4%, p=0.26 and 107±31ms vs 102±18ms, p=0.24 respectively). LVMD was prolonged in patients with subsequent AVB compared to patients with No-AVB (60±19ms vs 48±13ms, p<0.001) (Figure 1). LVMD predicted AVB after TAVI with area under the curve 0.71. LVMD predicted AVB independently of QRS duration (odds ratio 1.68; 95% confidence interval 1.23–2.3; p=0.001 by 10ms increments) (Table 1). Conclusion: LVMD predicted AVB after TAVI independent of QRS duration. LVMD may be of added value as a myocardial functional echocardiographic predictor of this important and frequent complication of TAVI. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): EACVI Research Grant 2020